Translocase of the Outer Mitochondrial Membrane 40 Is Required for Mitochondrial Biogenesis and Embryo Development in Arabidopsis - Hu, Ying; Zou, Wenxuan; Wang, Zhiqin; Zhang, Yuqin; Hu, Yuanyuan; Qian, Jie; Wu, Xuan; Ren, Yafang; Zhao, Jie (Frontiers in Plant Science, 2019)
In eukaryotes, mitochondrion is an essential organelle which is surrounded by double membrane system, including the outer membrane, intermembrane space and the inner membrane. The translocase of the outer mitochondrial membrane (TOM) complex has attracted enormous interest for its role in importing the preprotein from cytoplasm into mitochondrion. However, little is understood about the potential biological function of TOM complex in Arabidopsis. The aim of present study was to investigate how AtTOM40, a gene encoding the core subunit of the TOM complex, works in Arabidopsis. As a result, we found that lack of AtTOM40 disturbed embryo development and its pattern formation after the globular embryo stage, and finally caused albino ovules and seed abortion at the ratio of a quarter in the homozygous tom40 plants. Further investigation demonstrated that AtTOM40 is wildly expressed in different tissues, especially in cotyledons primordium during Arabidopsis embryogenesis. Moreover, we confirmed that the encoded protein AtTOM40 is localized in mitochondrion, and the observation of ultrastructure revealed that mitochondrion biogenesis was impaired in tom40-1 embryo cells. Quantitative real-time PCR was utilized to determine the expression of genes encoding outer mitochondrial membrane proteins in the homozygous tom40-1 mutant embryos, including the genes known to be involved in import, assembly and transport of mitochondrial proteins, and the results demonstrated that most of the gene expressions were abnormal. Similarly, the expression of genes relevant to embryo development and pattern formation, such as SAM (shoot apical meristem), cotyledon, vascular primordium and hypophysis, was also affected in homozygous tom40-1 mutant embryos. Taken together, we draw the conclusion that the AtTOM40 gene is essential for the normal structure of mitochondrion, and participates in early embryo development and pattern formation through maintaining the biogenesis of mitochondria. The findings of this study may provide new insight into the biological function of TOM40 subunit in higher plants.